2020
DOI: 10.3727/096504020x16056983169118
|View full text |Cite
|
Sign up to set email alerts
|

PNNandKCNQ1OT1Can Predict the Efficacy of Adjuvant Fluoropyrimidine-Based Chemotherapy in Colorectal Cancer Patients

Abstract: The benefit of adjuvant chemotherapy in early stages of colorectal cancer (CRC) is still disappointing and the prediction of treatment outcome quite difficult. Recently, through a transcriptomic approach, we evidenced a role of PNN and KCNQ1OT1 gene expression in predicting response to fluoropyrimidine-based adjuvant chemotherapy in stage III CRC patients. Thus, the aim of this study was to validate in an independent cohort of stage II-III CRC patients our previous findings. PNN and KCNQ1OT1 mRNA expression le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 62 publications
0
12
0
Order By: Relevance
“…14 Furthermore, some studies showed that PNN might cause resistance to chemotherapy, such as paclitaxel in ovarian cancer and fluoropyrimidine in colon cancer. 24 Given the inconsistency in PNN expression and function in cancers reported by previous studies, we aimed to investigate the subcellular localization and expression of PNN in RCC samples in the present study. We showed markedly increased PNN expression in RCC samples compared with that in adjacent normal tissues.…”
Section: Discussionmentioning
confidence: 99%
“…14 Furthermore, some studies showed that PNN might cause resistance to chemotherapy, such as paclitaxel in ovarian cancer and fluoropyrimidine in colon cancer. 24 Given the inconsistency in PNN expression and function in cancers reported by previous studies, we aimed to investigate the subcellular localization and expression of PNN in RCC samples in the present study. We showed markedly increased PNN expression in RCC samples compared with that in adjacent normal tissues.…”
Section: Discussionmentioning
confidence: 99%
“…In colon cancer tissues, DUXAP8, RP11-54H7.4, and RP11-138J23.1 show elevated expression in advanced tumor stages [49]. In colorectal cancer tissues, increased KCNQ1OT1 (as well as PNN) is associated with shorter DFS of individuals in stage III treated with 5-FU adjuvant therapy [50]. REG1CP, TPTE2P1, and DUXAP8 are upregulated in colorectal cancer patient samples and cell lines [51][52][53].…”
Section: Cancers Located In the Abdomen And Bonesmentioning
confidence: 99%
“…The PNN approach is a common data mining method that has been adapted to solve many pattern identification and classification issues (Lapucci et al 2020a ). In the PNN, the process is managed by a multilayer network consisting of four layers: an input layer, pattern layer, sum layer, and output layer.…”
Section: Introductionmentioning
confidence: 99%